Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/sj.jcbfm.9600411
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Quantification of [11C]-(+)-PHNO Binding in the Human Brain

Abstract: The kinetic modeling of [ 11 C]-( + )-PHNO binding to the dopamine D 2/3 receptors in six human volunteers using positron emission tomography (PET) is described. [ 11 C]-( + )-PHNO is the first agonist radioligand for the D 2/3 in humans and as expected showed high uptake in caudate, putamen, globus pallidus (GP) and ventral striatum, and low uptake in cerebellum. A two-tissue compartment model (2CM) with four parameters was necessary to adequately fit time-activity data in all regions. Although a 2CM provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 42 publications
7
83
1
1
Order By: Relevance
“…Moreover, motor circuitry 5-HT dysfunctions correlate with severity of tremor on posture and action. It is possible that resting tremor possesses a serotonergic substrate related more specifically to postsynaptic mechanisms, as evidenced by Doder et al 18 Our study utilized 11 C-DASB, a marker of presynaptic SERT only; thus, we were unable to detect any influence of the postsynaptic mechanisms involved in resting tremor in our patients.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…Moreover, motor circuitry 5-HT dysfunctions correlate with severity of tremor on posture and action. It is possible that resting tremor possesses a serotonergic substrate related more specifically to postsynaptic mechanisms, as evidenced by Doder et al 18 Our study utilized 11 C-DASB, a marker of presynaptic SERT only; thus, we were unable to detect any influence of the postsynaptic mechanisms involved in resting tremor in our patients.…”
mentioning
confidence: 49%
“…Postmortem 2 studies have shown loss of serotonergic (5-HT) projections in PD, although to a lesser extent than dopaminergic (DAergic) neurons. 11 C-DASB (11C-labeled 3-amino-4-[2-[(di(methyl)amino) methyl]phenyl]sulfanylbenzonitrile) PET imaging, a marker of serotonin transporter (SERT) binding, has shown that 5-HT dysfunction occurs early in PD 3 and that levels correlate with nonmotor symptoms such as depressive symptoms and alterations of body weight. 4,5 Whereas L-dopa and dopamine agonists successfully relieve bradykinesia and rigidity, the response of parkinsonian tremor is variable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…K 1 /k 2 for both target and reference regions were same in this simulation study; however, in clinical situation, sometimes K 1 /k 2 values may vary from regions to regions (Ginovart et al, 2007) and these difference may introduce errors in BP ND when the ratio K 1 /k 2 is fixed.…”
Section: Reliability Of Estimated Parametersmentioning
confidence: 91%